Gaps in communication between different staff groups and older adult patients foster unnecessary antibiotic prescribing for urinary tract infections in hospitals: a qualitative translation approach - Paula M. Saukko; Beryl A. Oppenheim; Mike Cooper; Emily K. Rousham (Antimicrobial Resistance and Infection Control, 2019)
Abstract Background Studies have reported large scale overprescribing of antibiotics for urinary tract infection (UTI) in hospitalised older adults. Older adults often have asymptomatic bacteriuria, and clinicians have been found to diagnose UTIs inappropriately based on vague symptoms and positive urinalysis and microbiology. However, the joined perspectives of different staff groups and older adult patients on UTI diagnosis have not been investigated. Methods Thematic analysis of qualitative interviews with healthcare staff (n = 27) and older adult patients (n = 14) in two UK hospitals. Results Interviews featured a recurrent theme of discrepant understandings and gaps in communication or translation between different social groups in three key forms: First, between clinicians and older adult patients about symptom recognition. Second, between nurses and doctors about the use and reliability of point-of-care urinary dipsticks. Third, between nurses, patients, microbiologists and doctors about collection of urine specimens, contamination of the specimens and interpretation of mixed growth laboratory results. The three gaps in communication could all foster inappropriate diagnosis and antibiotic prescribing. Conclusion Interventions to improve diagnosis and prescribing for UTIs in older adults typically focus on educating clinicians. Drawing on the sociological concept of translation and interviews with staff and patients our findings suggest that inappropriate diagnosis and antibiotic prescribing in hospitals can be fuelled by gaps in communication or translation between different staff groups and older adult patients, using different languages and technologies or interpreting them differently. We suggest that interventions in this area may be improved by also addressing discrepant understandings and communication about symptoms, urinary dipsticks and the process of urinalysis.